Paul Morawitz - N. A. Makatsariya; I. S. Kalashnikova; F. E. Yakubova (Акушерство, гинекология и репродукция)
Here, we describe the historical aspects of the life and scientific work of Paul Morawitz as well as his contribution to medicine.